Strategies for Enhancing Students' Numeracy Literacy in Primary Education - Bahtiar, Teguh Gunawan; Rosdiana, Yeti; Akromah; Rahayuning, Tuti; Zainal, Muhammad (International Conference on Elementary Education, 2025)
The persistently low performance of Indonesian students in numeracy, as consistently reflected in national and international assessments, indicates that numeracy instruction in primary schools still confronts substantial challenges. This study aims to identify and analyze various strategies that have been implemented to enhance numeracy literacy among primary school students in Indonesia. Employing a Systematic Literature Review (SLR) approach, 31 peer-reviewed articles published between 2018 and 2024 were systematically reviewed. The procedure involved selection based on inclusion criteria, content coding structured around strategic components, and thematic analysis of the instructional approaches utilized. The findings reveal five dominant strategies: the use of interactive media, contextual-thematic learning, collaborative-community-based approaches, differentiated instruction, and the integration of digital technology. The results further indicate that the efficacy of numeracy literacy enhancement is largely dependent on the alignment of the chosen strategies with the specific student context, the proactive role of the teacher, and the comprehensive support provided by the school and family environments. This study concludes that effective numeracy strategies must be integrative, adaptive, and contextually grounded to adequately meet the demands of 21st-century mathematics education. These findings are expected to serve as a practical and conceptual reference for teachers, curriculum developers, and educational researchers in designing effective and sustainable numeracy interventions at the primary education level.